Comparison and Sensitivity Investigations of a CALM and SALM Type Mooring System for Wave Energy Converters - Arthur Pecher; Aligi Foglia; Jens Peter Kofoed (Journal of Marine Science and Engineering, 2014)
A quasi-static analysis and sensitivity investigation of two different mooring configurations—a single anchor leg mooring (SALM) and a three-legged catenary anchor leg system (CALM)—is presented. The analysis aims to indicate what can be expected in terms of requirements for the mooring system size and stiffness. The two mooring systems were designed for the same reference load case, corresponding to a horizontal design load at the wave energy converter (WEC) of 2000 kN and a water depth of 30 m. This reference scenario seems to be representative for large WECs operating in intermediate water depths, such as Weptos, Wave Dragon and many others, including reasonable design safety factors. Around this reference scenario, the main influential parameters were modified in order to investigate their impact on the specifications of the mooring system, e.g. the water depth, the horizontal design load, and a mooring design parameter.